Establishing boundary conditions for multiple design elements congruent with taste expectations - Matthews, P; Simmonds, G; Spence, C (Elsevier, 2019)
Over the past two decades, a burgeoning literature has demonstrated the robust associations that exist between visual elements (‘cues’) on product packaging in the food and beverage category and consumer expectations regarding the taste of a product. However, to date, little research has examined if/how the individual effects demonstrated for such visual cues combine when multiple cues are presented together. Therefore, two experiments were designed to investigate whether manipulating the number (Experiment 1), and congruency (i.e., an association with a particular taste as identified by previous literature; Experiment 2) of word, colour, and background pattern angularity cues would influence people's taste expectations and associated evaluations. The results of Experiment 1 demonstrated that increasing the number of congruent cues on product packaging increased the strength of people's expectations concerning the relevant basic taste, with an apparent ‘ceiling effect’ hinted at. Experiment 2 extended this novel empirical finding by demonstrating that when colour and background pattern cues were associated with different basic tastes (i.e., the cues were, in some sense, ‘incongruent’), rather than counteracting one another, colour tended to dominate over background pattern in terms of determining the expected taste of the product. Taken together, these results suggest that stronger, or at least more salient, design cues dominate over weaker ones when they conflict in terms of their meaning (or corresponding taste).